Sous les vagues bleues, le paysage - Christophe Camus (Projets de Paysage)
In this article, we look back at the invention of the underwater landscape by the pioneers of marine hunting and diving. We have attempted to reconstruct a part of this invention taking as a starting point the simple notion that most of us, even those of us who are not divers, can now imagine and picture the ocean depths thanks to the efforts of Jacques-Yves Cousteau and other diving pioneers. The history of diving is well documented, but our study focuses on the ways in which it was described, narrated and shown in order to invent a landscape that for a long time had remained invisible and inaccessible to ordinary people. The article begins by looking back on the invisibility and inaccessibility of the depths of the "territory of the void" (The Lure of the Sea, Corbin, 1990), before providing a first glimpse of these depths by following an imaginary walk taken from Jules Verne’s Nautilus. Looking beyond the ancient fears and romanticised representations of the abyss, we investigate a first series of stories of exploratory, hunting and diving expeditions in places ranging from the tropical seas to the French Riviera that revealed the true nature of the abyss and at the same time invented modern subaquatic sports and leisure practices. Finally, remaining in the Mediterranean, we join Cousteau who, through his films and books, invents and puts on show an underwater landscape that is hospitable and can even be colonised or inhabited by humans.